2022
DOI: 10.1111/jonm.13810
|View full text |Cite
|
Sign up to set email alerts
|

The status of ethical behaviour in clinical nursing in three Chinese hospitals: A qualitative interview study

Abstract: Aim: We aim to explore the status of nurses' ethical behaviours in clinical practice and what contributes to nurses' unethical behaviours.Background: Nurses' ethical behaviours strongly impact the nurse-patient relationship and the quality of nursing services. Therefore, we must understand the status of clinical nurses' ethical behaviours and the causes of nurses' unethical behaviours.Methods: Focus group and in-depth semistructured interviews were conducted with 21 head nurses and nine nurses, respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…In another study, nurses estimated their own ethical competence to be at an average level [ 41 ]. Our study findings are in line with the literature [ 39 , 42 , 43 ]. The negative (low levels ethical attitude) ethical attitudes of the nurses who participated in our research may have resulted from the complex ethical problems experienced due to the critical importance of the patient group provided care for and the high workload and stress of the nurses.…”
Section: Discussionsupporting
confidence: 94%
“…In another study, nurses estimated their own ethical competence to be at an average level [ 41 ]. Our study findings are in line with the literature [ 39 , 42 , 43 ]. The negative (low levels ethical attitude) ethical attitudes of the nurses who participated in our research may have resulted from the complex ethical problems experienced due to the critical importance of the patient group provided care for and the high workload and stress of the nurses.…”
Section: Discussionsupporting
confidence: 94%
“…In China, entry criteria for SNs vary depending on the area of specialist care. Provinces and municipalities have also developed different entry criteria in their SNs training systems, resulting in uneven competencies and low recognition of SNs across the country (Ma et al, 2019;Zhang et al, 2012).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The scientific research ability of nurses is an important factor used to measure the quality of nursing education (Zhang et al, 2012).…”
Section: Current Situation Of Scientific Research Ability Of Snsmentioning
confidence: 99%
“…A study in Canada showed that 71% of ICU patients had no exercise, 28 and another survey in China showed that early exercise rate of patients with mechanically ventilation was only 19.2% . 29 To improve the implementation rate of early exercise in ICU, a professional multidisciplinary team (including doctors, nurses, rehabilitation physiotherapists, etc) is required, and the role of nurses is indispensable. 3,30,31 As the literature supporting early exercise expands, investigations of current clinical practice are necessary to inform implementation efforts.…”
Section: Introductionmentioning
confidence: 99%